Business plans for dummies. - Tiffany, Paul; Peterson, Steven (Steven D.); Barrow, Colin (For Dummies, 2022)
Plan to succeed as an entrepreneur--we show you how Business Plans For Dummies can guide you, as a new or aspiring business owner, through the process of creating a comprehensive, accurate, and useful business plan. In fact, it is just as appropriate for an already up-and running firm that realizes it's now time for a full-bore check-up, to ensure the business is in tip-top shape to meet the challenges of the globalized, digitized, and constantly changing 21st Century. This edition of is fully updated, featuring the most recent practices in the business world. Let us walk you through each step of the planning process. You'll find everything you need in this one book, so you can finally stop googling, close all those browser tabs, and get organized and get going. Updates to this new revision include knowing how to pivot when your situation changes, recognizing the need for diversity and inclusion in the workplace, where to tap the latest funding sources, and how to plan for a digital strategy, market disruption, and environmental sustainability. You'll also learn how today's globalized marketplace influences your business--and how you can use social media to influence your customers right back. Learn the ins and out of creating a business plan that will actually work Set effective goals and objectives so your business can find success Wow investors with your knowledge of today's important business trends Map out your finances, marketing plan, and operational blueprint--then confidently get to work! Challenge the traditional framework by building a business plan that's workable in today's reality. Dummies is here to help.